Wage coordination and the welfare state: Germany and Japan compared - Philip Manow (Max Planck Institute for the Study of Societies, 2000)
Is there a relation between welfare state regimes and national wage setting systems? Peter Swenson in his research on the historical dynamics of the US-American and Swedish welfare state has recently claimed that such a relation does indeed exist. The essay aims to check if this also holds true for the German and Japanese case. In the post-war period both countries have established systems of wage-bargaining that are less centralized than the Swedish system, but in which wages are highly coordinated both within and across sectors, and, subsequently, in which wage compression is relatively high as well. Thus, both countries are confronted with the same problems of wage- and welfare-drift and of firms' exit from the 'solidaristic' or coordinated wage setting that are so typical for Sweden. At the same time the German and Japanese welfare state differ from each other in almost all dimensions. Thus, both cases seem to be ideally suited to provide for a plausibility-check of the Swenson hypothesis. The essay reaches the conclusion that there is indeed ample evidence that both the German and the Japanese welfare state contributed critically to the stability of wage coordination in the era of high growth after World War II. They thus have to be understood as an integral part of the German and Japanese post-war growth model. – – Gibt es einen Zusammenhang zwischen Wohlfahrtsstaatsregimen und nationalen Systemen der Lohnkoordination? Peter Swenson hat diese Frage kürzlich in seiner Untersuchung der historischen Dynamik des US-amerikanischen und schwedischen Wohlfahrtsstaats bejaht. Der Aufsatz nimmt sich zum Ziel, Swensons These anhand des deutschen und japanischen Falls zu überprüfen. Sowohl in Deutschland als auch in Japan ist zwar der Grad der Zentralisierung der Lohnverhandlung geringer ausgeprägt als in Schweden, doch die Lohnkoordinierung innerhalb und zwischen den Sektoren ist hoch und führt in beiden Ländern zu relativ starker Lohnkomprimierung. Deutschland und Japan sind folglich mit ähnlichen Problemen der wage- und welfare drift und der Gefahr eines Ausscherens hoch produktiver Firmen aus der 'solidarischen' bzw. koordinierten Lohnpolitik konfrontiert, wie sie für das schwedische Modell typisch sind. Zugleich sind die Unterschiede zwischen dem deutschen und dem japanischen Wohlfahrtsstaat in so gut wie allen Dimensionen sehr ausgeprägt. Insofern scheint der Deutschland/Japan-Vergleich eine gute Überprüfungsmöglichkeit für die Swenson-Hypothese zu bieten. Der Aufsatz kommt zu dem Schluß, daß in der Tat viel empirische Evidenz dafür spricht, daß der Wohlfahrtsstaat in Deutschland und Japan in der Phase des rapiden wirtschaftlichen Wachstums ebenfalls einen wichtigen Beitrag zur Stabilisierung koordinierter Lohnverhandlungen geleistet hat und somit integraler Bestandteil des deutschen und japanischen Wachstumsmodells gewesen ist.
Keywords: 300